Pengaruh Penggunaan EM4 terhadap fermentasi Ampas Serai Wangi Terhadap Kandungan Bahan Kering, Kadar Abu Dan Bahan Organik - Syahro Ali Akbar; Deni Syah Putri; Harissatria Harissatria (Program Studi peternakan, 2022)
This study aimed to determine the effect of fermented citronella pulp using effective microorganisms (em4) using rice bran as a carbohydrate source on dry matter content, ash content, and organic matter. In this study, 400 grams of EM4 were used, 3680 grams of citronella pulp, and 320 grams of rice bran as a carbohydrate source. Completely randomized design 4 levels adding the rice bran with 4 replication used in this research. There were: A (5%), B (7%), C (9%), and D (11%). The variables observed in this study were dry matter content, ash content, and organic matter. The results of this study showed that the fermentation of citronella pulp with EM4 using rice bran as carbohydrates on dry matter content, ash content and organic matter gave no significant effect (P> 0.05). Giving rice bran as a carbohydrate source as much as 5% (Treatment A) in the process of making citronella dregs fermentation tends to be the best level (more cost-effective) compared to 7% (treatment B), 9% (treatment C) and 11% (treatment D) .